2003
DOI: 10.1034/j.1600-0633.2003.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction biology of pikeperch (Sander lucioperca (L.)) – a review

Abstract: Reproduction biology of pikeperch (Sander lucioperca (L.)) -a reviewUn resumen en espan˜ol se incluye detra´s del texto principal de este artı´culo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
92
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 42 publications
10
92
2
Order By: Relevance
“…The absolute fecundity (from 164.6 to 208.3 9 10 3 eggs) of pikeperch recorded in this study is similar to the results reported by Demska- Zakes and Zakes (2002) and Lappalainen et al (2003). Also, size of eggs showed no difference with the previous studies (Horvath et al 1984;Schlumbenger and Proteau 1996;Lappalainen et al 2003).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The absolute fecundity (from 164.6 to 208.3 9 10 3 eggs) of pikeperch recorded in this study is similar to the results reported by Demska- Zakes and Zakes (2002) and Lappalainen et al (2003). Also, size of eggs showed no difference with the previous studies (Horvath et al 1984;Schlumbenger and Proteau 1996;Lappalainen et al 2003).…”
Section: Discussionsupporting
confidence: 91%
“…The relative fecundity (from 88.0 to 144.6 9 10 3 eggs kg -1 ) of pikeperch obtained in this study is lower compared with Lappalainen et al (2003) (250 9 10 3 eggs kg -1 ) and to Schlumbenger and Proteau (1996) (200 9 10 3 eggs kg -1 ). The absolute fecundity (from 164.6 to 208.3 9 10 3 eggs) of pikeperch recorded in this study is similar to the results reported by Demska- Zakes and Zakes (2002) and Lappalainen et al (2003).…”
Section: Discussioncontrasting
confidence: 53%
“…Before the spawning season of zander under natural conditions, when the size of ripe oocytes is the largest in the gonads, the value of GSI can reach 14-19% (Lappalainen et al, 2002). The relative fecundity which is defined as the number of eggs per 1g of female varies between 150 and 400 eggs on average (Lappalainen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The relative fecundity which is defined as the number of eggs per 1g of female varies between 150 and 400 eggs on average (Lappalainen et al, 2002). However, there is no data about the GSI of zander females cultured in farm conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Higher temperatures can be expected to increase the growth rates of many fish species in the Baltic (MacKenzie et al 2007 and reference therein), implying a change in weight at age. Faster growth in turn causes earlier maturity in pikeperch populations adapted to warmer conditions (Lappalainen et al 2003). Therefore the Pärnu Bay pikeperch stock might be less sensitive to the catch of small fish in a future warmer climate.…”
Section: Discussionmentioning
confidence: 99%